On the Role of E‐F Region Coupling in the Generation of Nighttime MSTIDs During Summer and Equinox: Case Studies Over Northern Germany. Issue 5 (23rd May 2022) - Sivakandan, Mani; Martinis, Carlos; Otsuka, Yuichi; Chau, Jorge L.; Norrell, Jessica; Mielich, Jens; Conte, J. Federico; Stolle, Claudia; Rodríguez‐Zuluaga, J.; Shinbori, Atsuki; Nishioka, Michi; Tsugawa, Takuya
Abstract: Simultaneous observations from a 630 nm all‐sky airglow imager, GNSS‐TEC receivers, and an ionosonde are used to investigate the role of E‐ and F‐region coupling on the generation of medium‐scale traveling ionospheric disturbances (MSTIDs). The primary observations are OI 630 nm airglow images taken by an all‐sky imager in Kühlungsborn (54.07°N; 11.46°E, 53.79°N Mlat.), a site in northern Germany. Out of 226 nights of observations, MSTIDs were found only in 18 nights, demonstrating the low occurrence rate over Kühlungsborn. We focused on four MSTIDs events: two during the vernal equinox and two during summer. Coincident measurements of detrended GNSS‐TEC supported the presence of MSTIDs during the selected events, and simultaneous observations from the ionosonde in Juliusruh (54.60°N, 13.4°E, 54.02°N Mlat.) showed sporadic‐E (Es) layer and spread‐F activity in the E‐ and F‐region, respectively. We observed the onset of the observed MSTIDs to be around the 15°–20°E longitude and 60–45°N latitude belts. Additionally, we found that in each case, the onset of MSTIDs coincides with the presence of an Es layer with sporadic‐E trace is observed (foEs) exceeding 4 MHz. This suggests that an Es layer with foEs ≥ 4MHz was a source of the generation of these MSTIDs. Altitude of the Es layer could be another important factor in generating MSTIDs. The Es layer should exist at an altitude where Hall conductivity is large, as happened in the present study. Key Points: Nighttime medium‐scale traveling ionospheric disturbances (MSTIDs) occur less frequently over northern Germany than at lower latitude regions The presence of Es layers with sporadic‐E trace is observed greater than 4 MHz is a potential source for the onset of the observed MSTIDs The low occurrence rate and small amplitude of nighttime MSTIDs could be attributed to the dip angle dependence of the Es layer instability